Characterization of The Characters in The Social Network Movie - I Gusti Agung Ngurah Agung Yudha Pratama Arnawa Putra; Yana Qomariana; Putu Lirishati Soethama (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The purpose of this study was to identify the types of principal and scenario-dependent characters and investigate the characterization represented based on character types in The Social Network movie. The collecting data process was done by applying documentation method and note-taking technique. The collected data were analysed with the theory of characters proposed by Sanford and Garrod (2011) and theory of characterization by Lawrence (2017) in order to answer the problem of the study such as the types of principal and scenario-dependent characters are found and how is the characterization of the main characters of the movie. The research found that there are Mark Zuckerberg, Eduardo Saverin and Sean Parker as principal character in the movie and the other as a supportive characters. The characterization of Mark Zuckerberg is ambitious and socially awkward, displaying intense focus and brilliance but lacking interpersonal skills. Eduardo Saverin is empathetic and ethical, struggling with loyalty and traditional business values. Sean Parker is charismatic and visionary, with a persuasive, innovative mindset that drives strategic decisions and disrupts conventional norms.